Advancements in earthquake research and seismic risk analysis: An in-depth review centered on Malaysia - Sharifah Izzati, Syed Mustorpha; Saffuan, Wan Ahmad; Muhammad Aimran Amzar, Kamarudin; Alsakkaf, Hamdi Ahmed; Shafiq, Omair (Semarak Ilmu Publishing, 2026)
This paper provides an in-depth review of recent advancements in earthquake and seismic risk analysis research, specifically focusing on Malaysia. It highlights the need for a deep understanding of seismic risks to create better hazard preparedness and mitigation strategies. Using a systematic literature review method, the paper brings together a wide range of recent studies, modern methods, and key findings. It identifies major knowledge gaps and suggests new directions for future research. Additionally, this paper covers cutting-edge seismic monitoring technologies, advanced fault analysis techniques, and comprehensive seismic hazard assessment models to provide a thorough understanding of Malaysia's complex seismic landscape. It also addresses the economic implications of seismic events, emphasizing the significance of earthquake preparedness. Moreover, the study underscores the need for greater collaboration among scholars, policymakers, and practitioners from various sectors. It advocates for the development of integrated frameworks and policies to address the identified gaps and translate research insights into practical solutions. The conclusion calls for a united effort to boost Malaysia's resilience to seismic hazards through continuous innovation, shared expertise, and strategic policymaking. This thorough analysis not only aims to deepen the scientific understanding of seismic risks in Malaysia but also to inspire effective policies and build a community ready to tackle future seismic threats. By closing knowledge gaps and enhancing teamwork, this study helps pave the way for a more secure and prepared Malaysia.